Peningkatan Hasil Belajar Matematika pada Soal Cerita Materi Luas Bangun Datar Menggunakan Model Polya di Kelas IV SDN 20 Indarung - Muhammad Dzulkifli; Masniladevi Masniladevi; Fardatil Aini Agusti; Serly Safitri (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This research is motivated by the low mathematics learning outcomes of fourth-grade students of SD Negeri 20 Indarung on the topic of area of ​​flat shapes due to teacher-centered learning that makes students less active in understanding concepts and solving problems. This research aims to improve mathematics learning outcomes through the application of the Polya problem-solving model. The type of research used is Classroom Action Research with qualitative and quantitative approaches implemented in two cycles through the stages of planning, action implementation, observation, and reflection. The research subjects were 30 fourth-grade students. Data collection techniques were carried out through tests and non-tests, namely learning outcome tests to measure aspects of knowledge and skills and observation sheets to observe the activities of teachers and students during learning. Quantitative data were analyzed by calculating the average value of learning outcomes, while qualitative data were analyzed descriptively to describe the learning process. The results of the study showed an increase in learning outcomes, marked by an increase in the average aspect of knowledge from 50.73 in cycle I to 81.36 in cycle II and the aspect of skills from 60 to 84.17. These findings indicate that the Polya problem-solving model is effective in improving mathematics learning outcomes on the material of area of ​​flat shapes